Localization and Cellular Amounts of the WalRKJ (VicRKX) Two-Component Regulatory System Proteins in Serotype 2 Streptococcus pneumoniae - Wayne, Kyle J. (American Society for Microbiology (ASM), 2010)
The WalRK two-component regulatory system coordinates gene expression that maintains cell wall homeostasis and responds to antibiotic stress in low-GC Gram-positive bacteria. Phosphorylated WalR (VicR) of the major human respiratory pathogen Streptococcus pneumoniae (WalR(Spn)) positively regulates transcription of several surface virulence genes and, most critically, pcsB, which encodes an essential cell division protein. Despite numerous studies of several species, little is known about the signals sensed by the WalK histidine kinase or the function of the WalJ ancillary protein encoded in the walRK(Spn) operon. To better understand the functions of the WalRKJ(Spn) proteins in S. pneumoniae, we performed experiments to determine their cellular localization and amounts. In contrast to WalK from Bacillus subtilis (WalK(Bsu)), which is localized at division septa, immunofluorescence microscopy showed that WalK(Spn) is distributed throughout the cell periphery. WalJ(Spn) is also localized to the cell surface periphery, whereas WalR(Spn) was found to be localized in the cytoplasm around the nucleoid. In fractionation experiments, WalR(Spn) was recovered from the cytoplasmic fraction, while WalK(Spn) and the majority of WalJ(Spn) were recovered from the cell membrane fraction. This fractionation is consistent with the localization patterns observed. Lastly, we determined the cellular amounts of WalRKJ(Spn) by quantitative Western blotting. The WalR(Spn) response regulator is relatively abundant and present at levels of ≈6,200 monomers per cell, which are ≈14-fold greater than the amount of the WalK(Spn) histidine kinase, which is present at ≈460 dimers (920 monomers) per cell. We detected ≈1,200 monomers per cell of WalJ(Spn) ancillary protein, similar to the amount of WalK(Spn).